2015
DOI: 10.1093/ije/dyv172
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving reduces mortality risk for most caregivers: a census-based record linkage study

Abstract: This large population-based study confirms that for the majority of caregivers the beneficial effects of caregiving in terms of short-term mortality risk appear to outweigh any negative effects, even among people with significant health problems. These results underscore the need for a reappraisal of how caregiving is perceived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 42 publications
10
91
1
Order By: Relevance
“…In fully adjusted models, each had an equivalent association with lowered mortality risk, with estimated effects similar to findings in existing meta-analyses of both volunteering [3,6] and caregiving [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In fully adjusted models, each had an equivalent association with lowered mortality risk, with estimated effects similar to findings in existing meta-analyses of both volunteering [3,6] and caregiving [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 64%
“…Two recent overviews, by Brown & Brown [13] and Roth et al [14], have argued for more balance, suggesting that "policy reports, media portrayals, and many research reports commonly present an overly dire picture' while ignoring alternative positive findings. It is now recognised that many caregivers report benefit from caregiving [15,16] and population-based mortality studies generally find that caregivers have reduced mortality compared with non-caregivers [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, findings by O'Reilly et al . () of a negative link between care‐giving and mortality in Northern Ireland suggest that selective mortality of care givers was unlikely to be an issue in the NILS. Regarding long‐term employment and care‐giving transitions, the NILS only has data for the two Census years 2001 and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In a Census‐based mortality study performed in Northern Ireland, O'Reilly et al . () found that moderate care‐giving responsibilities were associated with better health and a lower risk of mortality and suicide (O'Reilly et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the effects of a partner's caregiving on mortality have shown inconsistent results. Some studies have shown an association with all‐cause mortality and cardiovascular disease (CVD) risks, whereas others have not found any such association . The impact of the caregiving burden on mortality might differ between age and sex based on the caregiving burden differences between the two factors.…”
Section: Introductionmentioning
confidence: 99%